2021
DOI: 10.1093/humrep/deab233
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive, label-free optical analysis to detect aneuploidy within the inner cell mass of the preimplantation embryo

Abstract: STUDY QUESTION Can label-free, non-invasive optical imaging by hyperspectral autofluorescence microscopy discern between euploid and aneuploid cells within the inner cell mass (ICM) of the mouse preimplantation embryo? SUMMARY ANSWER Hyperspectral autofluorescence microscopy enables discrimination between euploid and aneuploid ICM in mouse embryos. WHAT IS KNOWN ALREADY … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…In the field of reproductive biology, hyperspectral microscopy demonstrated the capacity to discern between good and poor quality bovine embryos (Sutton-McDowall et al 2017;Santos Monteiro et al 2021) and oocytes denuded of cumulus cells from young and aged mice (Bertoldo et al 2020). Additionally, mathematical algorithms applied to autofluorescence signals obtained from hyperspectral imaging were able to discriminate between different cell populations (Gosnell et al 2016a;Sutton-McDowall et al 2017;Habibalahi et al 2019;Mahbub et al 2021;Tan et al 2022b). Our recent work successfully demonstrated the ability of hyperspectral imaging to separately measure metabolism in the oocyte and cumulus cell compartments of the intact COC, when compared with conventional laser scanning confocal microscopy (Fig.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…In the field of reproductive biology, hyperspectral microscopy demonstrated the capacity to discern between good and poor quality bovine embryos (Sutton-McDowall et al 2017;Santos Monteiro et al 2021) and oocytes denuded of cumulus cells from young and aged mice (Bertoldo et al 2020). Additionally, mathematical algorithms applied to autofluorescence signals obtained from hyperspectral imaging were able to discriminate between different cell populations (Gosnell et al 2016a;Sutton-McDowall et al 2017;Habibalahi et al 2019;Mahbub et al 2021;Tan et al 2022b). Our recent work successfully demonstrated the ability of hyperspectral imaging to separately measure metabolism in the oocyte and cumulus cell compartments of the intact COC, when compared with conventional laser scanning confocal microscopy (Fig.…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…Such changes alter the autofluorescence signal of cells and can be quantified and correlated using mathematical approaches, thus enabling discrimination between different cell populations (Gosnell et al 2016). Dr. Dunning's team has recently demonstrated that hyperspectral imaging can be used to successfully distinguish healthy euploid from aneuploid cells within the ICM of mouse preimplantation embryos (Tan et al 2021). Future studies will determine the effectiveness of hyperspectral imaging at detecting aneuploidy in human embryos, which would ultimately provide an affordable and practical clinical tool for determining embryo health non-invasively.…”
Section: Novel Technologies In Reproductionmentioning
confidence: 99%
“…As label-free optical imaging to determine embryo developmental potential increase in popularity [ 21 , 22 ], it is imperative that the impact of different wavelengths of light on the preimplantation embryo is carefully characterized. Mapping the stress tolerance embryos show for each wavelength may be advantageous in identifying how damage can be mitigated in clinical manipulation and modern imaging techniques.…”
Section: Introductionmentioning
confidence: 99%